After a Decade of Human Papillomavirus Vaccination, How to Bend the Vaccination Uptake Curve Upward. Issue 1 (January 2017) - Spitzer, Mark
Abstract : The time has come for clinicians to strongly advocate for the vaccination of 11- and 12-year-old girls and boys according to the Advisory Committee on Immunization Practices guidelines.